The importance of ownership I - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Busani Bafana talks to Inviolatta Moyo of the Western Region Foundation in Zimbabwe, an organisation that puts great emphasis on training its project holders in business skills.